AN ANALYSIS OF STUDENTS’ STRATEGIES IN OVERCOMING THEIR SPEAKING ANXIETY AT SMP NEGERI 5 KOTAMOBAGU - Anggelia Natalsya Emor; Noldy Pelenkahu; Paula Hampp (Program Studi Pendidikan Bahasa Inggris, 2023)
Speaking anxiety is a prevalent issue among students across different educational levels, and it can hinder their ability to communicate effectively in public. This research aimed to examine the underlying causes of speaking anxiety in students and explore the coping strategies they employ to address it. The study adopted a qualitative approach and involved 8th-grade students at SMP Negeri 5 Kotamobagu. Data collection was conducted through participant observation and in-depth interviews. The study's findings indicated that students' speaking anxiety primarily stems from two sources: firstly, internal factors related to their own self-perception, influenced by various factors like a lack of self-confidence, insufficient preparation and training, the fear of making mistakes, concerns about negative judgments from others, or inherent shyness. Secondly, external factors tied to classroom activities, including the pressure exerted by teachers to speak spontaneously or an unsupportive classroom environment. Students employ a range of strategies to cope with speaking anxiety, including triggering a relaxation response, thorough preparation and practice, adjusting their thought patterns and attitudes, envisioning successful outcomes, and incorporating physical movement. The study's results emphasize the crucial role of positive thinking and the support provided by parents, teachers, and peers in assisting students in overcoming speaking anxiety, thereby enhancing their self-assurance and level of readiness.